The effects of director ownership on capital adequacy and risk taking among private commercial banks in Bangladesh within the basel capital adequacy framework / Md. Mohidul Islam … [et al.] - Islam, Md. Mohidul; Bhuiyan, Abul Bashar; Md Kassim, Aza Azlina; Rasli, Salina (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
The study examines the effect of director’s ownership on capital adequacy and risk taking of private commercial banks in Bangladesh within the Basel capital adequacy framework. The secondary panel data were obtained from annual report of quoted 20 private commercial Banks in Bangladesh as compiled in the Dhaka Stock Exchange for the period 2015 to 2019. The study found that the director’s ownership concentration plays important role on capital formation that contribute to reduce excess risk taking. Particularly, the effective director’s ownership can be explained within the agency theory context, where directors are regarded as more risk appetite because of the exercise and employment risk. However, the presence of director’s ownership in capital adequacy influence on the risk taking practices in financial industries. These results support the research on capital formation and risk taking. The results of the study add a new dimension to the capital mechanism research that could be a valuable source of knowledge for policy makers and regulators in private commercial. As this study cover the role of director’s ownership on capital adequacy and risk taking, it could be useful for capital formation, regulation and policy making.